2020
DOI: 10.1177/0958305x20946483
|View full text |Cite
|
Sign up to set email alerts
|

Offshore wind energy status, challenges, opportunities, environmental impacts, occupational health, and safety management in India

Abstract: Offshore wind is at its infancy in terms of technology and capacities in India. The Ministry of New and Renewable Energy (MNRE) announced medium and long term offshore targets of 5 GW and 30 GW by 2022 and 2030, respectively. The location of the first offshore wind park has recently been identified, and the Solar Energy Corporation of India (SECI) has signed a contract with the Government of Gujarat to establish the 1000 MW of offshore wind energy capacity by 2019. To achieve the ambitious targets, India will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…e) Equipment, machines, and objects must function safely according to their intended use, with operational controls designed according to human capabilities. f) To limit the repercussions of accidents, incidents, and injuries, the proper emergency response must be provided (Charles Rajesh Kumar et al, 2021). The following principles are essential for comprehending the relationship between disaster prevention and uninterrupted production: a) Sometimes, accident prevention is viewed as a social burden rather than a crucial aspect of disorder prevention.…”
Section: Work Safetymentioning
confidence: 99%
“…e) Equipment, machines, and objects must function safely according to their intended use, with operational controls designed according to human capabilities. f) To limit the repercussions of accidents, incidents, and injuries, the proper emergency response must be provided (Charles Rajesh Kumar et al, 2021). The following principles are essential for comprehending the relationship between disaster prevention and uninterrupted production: a) Sometimes, accident prevention is viewed as a social burden rather than a crucial aspect of disorder prevention.…”
Section: Work Safetymentioning
confidence: 99%
“…Now, the focus has turned to the stronger wind resource area off Tamil Nadu. India has announced a national target of generating 5 GW by 2022 and 30 GW by 2030 ( IANS ; Kumar J et al 2020 ); however, the first plan seems to be no longer feasible and the second plan would require rapid deployment. The cost per MW offshore wind generation is comparatively higher than onshore because of developing structures in the marine environment.…”
Section: New Developments In Wind Energy Sectormentioning
confidence: 99%
“…These factors have made the researchers work in computational fluid dynamics to improve turbine efficiency. 40,41 The exposure of micro energy applications to urban environments involving complex modeling was formulated by researchers recently. Cheng et al 42 investigated the effects of flow fields over different layers and analyzed the roughness effects of the turbine in a complicated scenario.…”
Section: Wind Resource Assessment In An Urban Environmentmentioning
confidence: 99%
“…79,80 They listed that many technological modifications need to be made on the wind turbine to enhance its functionality in unfavorable conditions, establish accuracy in wind measurement, manufacture with local bodies, and robust transportation. 41,81 Kulkarni et al 82 analyzed the impact of climatic changes on wind persistence in Indian offshore conditions. The research identified four significant locations and was validated using different techniques.…”
Section: Causes For Issues Of a Small-scale Wind Turbine In The Urban...mentioning
confidence: 99%